Diversity of high risk human papilloma viruses in women treated with antiretroviral and in healthy controls and discordance with cervical dysplasia in the South of Benin. - CAPO-CHICHI, D. CALLINICE; AGUIDA, Blanche; CHABI, Nicodeme; ACAPKO-EZIN, Jocelyn; SOSSAH-HIFFO, Jonas; AGOSSOU, Videhouenou Komlan; ANAGBLA, Toussain; ZANNOU, Marcel; HOUNGBE, FABIEN; SANNI, AMBALIOU (My University, 2016)
Abstract BACKGROUND: High risk oncologic Human Papilloma Virus (HPV) is one of the leading causes of cervical cancer worldwide. We investigated HPV genotypes among women living or not with Human Immuno-deficiency Virus (HIV) in two major hospitals in the south of the republic of BENIN in the city of Cotonou. Our objective is to investigate the association of high risk-HPV to cervical dysplasia among women under stringent anti-retroviral (ARV) treatment and in controls without HIV. METHODS: The investigation was carried out within 1 year period in two groups of adult women: one group with HIV1 infection and under ARV therapy in the National University Hospital (CNHU-HKM) designated as CH group (n = 86); and one control group without HIV infection and attending the hospital Mènontin for routine gynecologic checkup and designated as ME group (n = 86). Cells derived from cervical uterine smears (CUS) were used for this investigation. The samples in ME group were selected to have similar lamin A/C profile with CH group. HPV genotypes were assessed by polymerase chain reaction (PCR) while lamin A/C expression profile was assessed by western blotting to corroborate the risk of cervical dysplasia. RESULTS: HPV56 is dominant in CH group while HPV66 is dominant in ME group. 31 % of women in CH group are infected with HPV compared to 23 % in ME group. Quadruple and quintuple HPV infections are more observed among CH group but not in ME group making HPV counts of 43 in CH group and 27 in ME group. Cervical dysplasia are present in 5 % (4/86) of women in CH group and in 1 % (1/86) of women in ME group at the time of CUS collection. The adjustment of the risk to develop cervical cancer in the future related to HPV infection and the total loss of lamin A/C is not significantly different in both groups. CONCLUSION: Women living with HIV are more sensitive to multiple HPV infection but not all HPV infections generated cervical dysplasia. The effectiveness of antiretroviral therapy in CH group may reduce significantly the frequency of cervical dysplasia.
Keywords: ARV; Cervical dysplasia; HIV; HPV; lamin A/C deficiency